The Role of Educational Tourism for Indonesian Development - Kadek Ayu Ekasani; Ni Kadek Ajeng Wangi Bhuanaputri; Paulin Yosephanny; Felicia Johny Alberta (Institut Pariwisata dan Bisnis Internasional, 2020)
Educational Tourism is one of the types of tourism in Indonesia. There are still limited studies that attempt to discover the relationship between tourism education and education tourism (edu-tourism). Educational Tourism is one of the types of tourism activities that has been recognized by the Indonesian government, which is a field trip related to an activity or trip whose purpose is for recreation or entertainment and contains educational activities in it. The data method is done by interview was used in collecting the data to get some information from local people or society, and data is descriptive qualitative. The results showed that English educational tourism through the phenomenon of Kampung Inggris is one of the Educational Tourism destinations in Indonesia. Educational Tourism has many benefits, such as creating jobs, improving the educational system, and increasing young generations' competitiveness. The role of education can make the country is able to have highly developed and foremost competitiveness.